EVALUATION OF WATER FROM BOKRO STREAM FOR IRRIGATION AND ITS EFFECT ON SOIL (Journal of Science and Technology, 2016)
This study focused on evaluating the water quality of the Bokro stream for its suitability for irri- gation purposes.  Among the water quality parameters examined were pH, total dissolved solids, conductivity, dissolved oxygen, hardness, major ions and concentration of some trace metals. The results revealed that most of the parameters examined were below the FAO limits for irriga- tion water. The results also indicated that nutrient concentrations (Sulphate, Nitrate-Nitrogen and Phosphate-Phosphorus) from the stream were far below the usual ranges in irrigation wa- ter. Based on values calculated for Sodium Adsorption Ratio and electrical conductivity, the wa- ter source could be described as possessing low salinity hazard and therefore no permeability problems are expected for the soils. In addition, human activities along the banks of the stream and inflow of untreated domestic sewage from communities in the catchment area of the stream were found to have great impact on the quality of water from the stream. Water from the stream will have no adverse effect on the soil when it is use for irrigation.